2015
DOI: 10.1007/s00590-015-1720-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of asymptomatic bacteriuria in knee arthroplasty patients and subsequent risk of prosthesis infection

Abstract: Asymptomatic bacteriuria presents a low prevalence. We have not found any case of arthroplasty infection from urinary focus in patients with asymptomatic bacteriuria whether they received or not specific antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 23 publications
3
21
0
Order By: Relevance
“…The prevalence of preoperative bacteriuria was 6.8%, which is similar to two earlier Spanish studies [12,15] and slightly lower than in other studies [8,13,14]. There was no association between preoperative bacteriuria and postoperative surgical site infection or PJI.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The prevalence of preoperative bacteriuria was 6.8%, which is similar to two earlier Spanish studies [12,15] and slightly lower than in other studies [8,13,14]. There was no association between preoperative bacteriuria and postoperative surgical site infection or PJI.…”
Section: Discussionsupporting
confidence: 84%
“…In a more recent study, Cordero-Ampuero et al [12] found no association between preoperative bacteriuria and postoperative infection following hip replacement, and treating the bacteriuria with antibiotics had no effect on the incidence of infection. The same research group reported similar results for knee replacements [15]. Unlike earlier studies, the current study takes into account the effect of both chronic diseases and outpatient antibiotic use.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…[9][10][11][12][13] However, there remains a lack of good evidence that treating asymptomatic bacteriuria reduces the risk of subsequent prosthetic joint infection. Published studies are all small, with insufficient power to generate convincing results.…”
Section: Association Not Causationmentioning
confidence: 99%